2017
DOI: 10.2527/jas.2016.0664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potential detoxifying agents on growth performance and deoxynivalenol (DON) urinary balance characteristics of nursery pigs fed DON-contaminated wheat1,2

Abstract: Two experiments were conducted to evaluate potential detoxifying agents on growth of nursery pigs fed deoxynivalenol (DON)-contaminated diets. Naturally DON-contaminated wheat (6 mg/kg) was used to achieve desired DON levels. In a 21-d study, 238 pigs (13.4 ± 1.8 kg BW) were used in a completely randomized design with a 2 × 2 + 1 factorial arrangement. Diets were: 1) Positive control (PC; < 0.5 mg/kg DON), 2) PC + 1.0% Product V (Nutriquest LLC, Mason City, IA), 3) Negative control (NC; 4.0 mg/kg DON), 4) NC +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…As expected, our results showed that RES supplementation improved BW gain, ADG and gain/feed, which was in accordance with the findings of previous polyphenol-investigated studies [ 13 , 23 , 34 ]. Additionally, we observed that DON significantly impaired the growth performance of piglets, which was consistent with the results of previous studies [ 33 , 35 , 36 ]. However, RES supplementation did not significantly prevent the DON-induced reduction in growth performance.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, our results showed that RES supplementation improved BW gain, ADG and gain/feed, which was in accordance with the findings of previous polyphenol-investigated studies [ 13 , 23 , 34 ]. Additionally, we observed that DON significantly impaired the growth performance of piglets, which was consistent with the results of previous studies [ 33 , 35 , 36 ]. However, RES supplementation did not significantly prevent the DON-induced reduction in growth performance.…”
Section: Discussionsupporting
confidence: 93%
“…FA4 resulted in commensurate ADG and ADFI to PC and superior G:F than all diets in wk 1. Similarly, adding SMB to a diet with 4 ppm DON resulted better ADG and G:F compared with the PC diet (0.05 ppm; Frobose et al, 2017 ). Several other studies have also shown that FA containing SMB mitigated negative effects of DON growth performance in pigs ( Patience et al, 2014 ; Bich et al, 2015a ; Frobose et al, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…Although we are attributing pig responses to DON and its metabolites (e.g., 15-ADON, 3-Acetyl DON), we cannot preclude impact of other mycotoxins in the corn sample even though they were detected at lower levels. The decrease in assayed DON in NC + FA4 relative to NC was attributed to the formation of DON-sulfonate, a nontoxic product formed by the reaction between SMB and DON during hydrothermal conditions of pelleting ( Dänicke et al, 2005 ; Frobose et al, 2017 ). Pigs fed NC diet exhibited 16% and 12% reduction in ADG and ADFI relative to PC pigs after 7 days of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be degraded back to DON under physiological conditions as it has been put in evidence in the urinary balance experiment carried out by Frobose (Frobose et al, 2017). It can be degraded back to DON under physiological conditions as it has been put in evidence in the urinary balance experiment carried out by Frobose (Frobose et al, 2017).…”
Section: Ochratoxin Amentioning
confidence: 94%